Polymer solid electrolyte and preparation method thereof

By using PEO-type copolymers containing crosslinkable functional groups and gaseous polar compounds in polymer solid electrolytes to form a three-dimensional network structure, the problem of low ionic conductivity of polymer solid electrolytes in the prior art is solved, and efficient ionic conductivity improvement and safety enhancement are achieved.

CN119731830APending Publication Date: 2025-03-28LG ENERGY SOLUTION LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380060521.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-12
Filing Date
2023-10-13
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing polymer solid electrolytes are difficult to improve ionic conductivity and there is a risk of safety when adding liquid electrolytes or solvents.

Method used

A three-dimensional network structure is formed to improve ionic conductivity by adding PEO-type copolymers containing crosslinkable functional groups to the polymer solid electrolyte and containing or bonding polar compounds in a gaseous form.

Benefits of technology

It is achieved to significantly improve the ionic conductivity of the polymer solid electrolyte without damaging mechanical properties, and enhance the safety and reliability of the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005275803390000031
    Figure BDA0005275803390000031
  • Figure BDA0005275803390000032
    Figure BDA0005275803390000032
  • Figure BDA0005275803390000033
    Figure BDA0005275803390000033
Patent Text Reader

Abstract

The invention relates to a polymer solid electrolyte and a preparation method thereof. The polymer solid electrolyte includes: a polymer including a PEO (polyethylene oxide)-based copolymer containing a crosslinkable functional group; and a polar compound wherein at least a portion of the crosslinkable functional groups form a crosslinking bond to each other such that the polymer forms a three-dimensional network structure, and wherein the polar compound is contained in the three-dimensional network structure in a gaseous state or bonded to a polymer chain.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0132764 filed on October 14, 2022, and Korean Patent Application No. 10-2023-0136061 filed on October 12, 2023, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference in their entirety.

[0003] The present invention relates to a polymer solid electrolyte and a preparation method thereof. Background Art

[0004] Lithium-ion batteries using liquid electrolytes have a structure in which the negative electrode and the positive electrode are defined by a separator, so when the separator is damaged by deformation or external impact, a short circuit may occur, causing dangers such as overheating or explosion. Therefore, it can be said that the development of a solid electrolyte that can ensure safety is a very important issue in the field of lithium-ion secondary batteries.

[0005] The advantages of lithium secondary batteries using solid electrolytes are that they have enhanced safety, prevent leakage of electrolytes to improve battery reliability, and help manufacture thin batteries. In addition, lithium metal can be used as a negative electrode to increase energy density. Therefore, in addition to compact secondary batteries, this lithium secondary battery using solid electrolytes is expected to be applied to high-capacity secondary batteries for electric vehicles and has attracted much attention as a next-generation battery.

[0006] Among solid electrolytes, composite electrolytes of polyethylene oxide (PEO) and lithium salts have the advantage of having higher ignition stability than conventional liquid electrolytes, but due to the high crystallinity of polyethylene oxide (PEO), it is difficult to prepare polymer solid electrolytes with improved ionic conductivity. In other words, the high crystallinity of the polymer hinders the chain mobility of the polymer chain, and therefore, the movement of lithium ions within the polymer solid electrolyte is restricted, which makes it difficult to improve the ionic conductivity of the polymer solid electrolyte.

[0007] In order to overcome the limitations of conventional polymer solid electrolytes, attempts have been made to change the structure of crystalline polymers or add separate plasticizers to the polymers to improve the mobility of polymer chains, thereby enhancing the ionic conductivity of polymer solid electrolytes. However, solid polymer electrolytes prepared by using such structural deformation of polymers and adding plasticizers may have difficulty in increasing the ionic conductivity above the 0.1 mS / cm level.

[0008] Attempts have been made to improve ionic conductivity by directly adding a liquid electrolyte or solvent to a polymer solid electrolyte, but this can be classified as a technology for semi-solid-state battery electrolytes in which solids and liquids coexist rather than a pure solid-state battery solid electrolyte. The improvement in ionic conductivity is not sufficient, and a large amount of liquid electrolyte still needs to be injected, so it is difficult to completely solve the problem of reduced safety due to liquid leakage, etc.

[0009] Therefore, in addition to polymer solid electrolytes prepared by changing the structure of the polymer, adding a separate plasticizer, or immersing the solid electrolyte in a liquid electrolyte, it is necessary to develop a technology that can improve the ionic conductivity of the electrolyte as a simple solid electrolyte for all-solid-state batteries.

[0010] [Prior art literature]

[0011] [Patent Document]

[0012] (Patent Document 0001) Japanese Patent Application Publication No. 1994-124713 Summary of the invention

[0013] [Technical issues]

[0014] An object of the present disclosure is to provide a polymer solid electrolyte that can improve ion conductivity even when a very small amount of a polar compound (eg, a polar solvent compound) is added to the polymer solid electrolyte in a non-liquid state, and a method for preparing the same.

[0015] Another object of the present disclosure is to provide an all-solid-state battery, which includes the above-mentioned polymer solid electrolyte, thereby exhibiting improved ionic conductivity, etc.

[0016] [Technical solution]

[0017] According to one embodiment of the present disclosure, a polymer solid electrolyte is provided, comprising: a polymer comprising a PEO (polyethylene oxide) type copolymer containing a cross-linkable functional group; and a polar compound, wherein at least a portion of the cross-linkable functional groups form cross-links with each other so that the polymer forms a three-dimensional network structure, and wherein the polar compound is contained in the three-dimensional network structure in a gaseous state or bonded to a polymer chain.

[0018] In polymer solid electrolytes, gaseous polar compounds are dispersed between polymer chains forming a three-dimensional network structure, or can be adsorbed or bonded to the surface or interior of the polymer chains.

[0019] In addition, the polymer solid electrolyte may further include a crosslinking agent. In this case, at least a portion of the crosslinkable functional groups may form crosslinked bonds with each other through the crosslinking agent.

[0020] In polymer solid electrolytes, PEO-based copolymers may contain one or more, or two or more crosslinkable functional groups. The crosslinkable functional groups are bonded to the chains of PEO-based copolymers by alkylene linkers or alkylene oxide linkers having 0 to 10 carbon atoms (wherein the alkylene linker having 0 carbon atoms represents a single bond), and may be selected from a functional group consisting of a hydroxyl group, a carboxyl group, an isocyanate group, a nitro group, a cyano group, an amine group, an amide group, an epoxy group, and an allyl group.

[0021] In addition, the polymer solid electrolyte may further include a lithium salt dispersed on the polymer forming a three-dimensional network structure, wherein the lithium salt may be contained in a state of at least partially dissociated cations and anions. The cations and / or anions may exist in a state bound to the polymer and may move during charge / discharge of the battery.

[0022] In a specific embodiment, the PEO (polyethylene oxide)-based copolymer of the polymer solid electrolyte may be a copolymer containing repeating units of the following Chemical Formulas 1 to 3:

[0023] [Chemical formula 1]

[0024]

[0025] [Chemical formula 2]

[0026]

[0027] [Chemical formula 3]

[0028]

[0029] Wherein, in Chemical Formulas 1 to 3, R1 represents -CH2-O-(CH2-CH2-O) k -R3, k is 0 to 20, R3 represents an alkyl group having 1 to 5 carbon atoms, R2 represents a substituent formed by bonding to the polymer chain one or more crosslinkable functional groups selected from the group consisting of hydroxyl, carboxyl, isocyanate, nitro, cyano, amine, amide, epoxy and allyl groups through an alkylene linker having 0 to 10 carbon atoms or an oxyalkylene linker (wherein the alkylene linker having 0 carbon atoms represents a single bond), and l, m and n are the number of repetitions of the repeating unit, wherein l and n are each independently an integer from 1 to 1000, and m is an integer from 0 to 1000.

[0030] On the other hand, in such a polymer solid electrolyte, the content of the polar compound may be 0.1 wt % or more and less than 10 wt % based on the total weight of the polymer solid electrolyte.

[0031] In addition, the polar compound may include at least one selected from the group consisting of carbonate compounds and sulfonyl compounds, and may be a polar compound derived from a carbonate solvent or a sulfonyl solvent and contained in a gaseous state. More specifically, the polar compound may include at least one selected from the group consisting of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC) and sulfolane.

[0032] On the other hand, according to another embodiment of the present disclosure, a method for preparing a polymer solid electrolyte of the above-mentioned embodiment is provided, the method comprising the following steps: (S1) preparing a polymer in which a PEO (polyethylene oxide) type copolymer containing a cross-linkable functional group is cross-linked; and (S2) vapor depositing a polar solvent on the polymer prepared in step (S1).

[0033] In this preparation method, the cross-linking reaction of step (S1) may be performed in the presence of at least one additive selected from the group consisting of a cross-linking agent and an initiator.

[0034] On the other hand, in the preparation method, the polar solvent may be a polar solvent corresponding to the polar compound of one embodiment.

[0035] Furthermore, in the preparation method, in step (S2), vapor of a polar solvent is deposited on the polymer so that the content of the polar solvent is 0.1 wt % or more and less than 10 wt % based on the total weight of the polymer solid electrolyte.

[0036] According to another embodiment of the present disclosure, an all-solid-state battery is provided, comprising: a positive electrode; a negative electrode; and an electrolyte layer, wherein the electrolyte layer is interposed between the positive electrode and the negative electrode and comprises the polymer solid electrolyte of one embodiment described above.

[0037] [Beneficial Effects]

[0038] The polymer solid electrolyte according to one embodiment of the present disclosure improves the mobility of polymer chains without deforming or breaking the material while maintaining the inherent structural properties of the polymer, thereby improving the ionic conductivity of the polymer solid electrolyte.

[0039] In addition, the polymer solid electrolyte contains a very small amount of gaseous polar compounds, which can improve the ionic conductivity and mechanical properties of the polymer solid electrolyte.

[0040] Furthermore, when a polar solvent is included in a polymer solid electrolyte by vapor deposition, gelation is prevented, the relaxation time of internal polymer chains is delayed, and the mobility of polymer chains is improved, thereby improving ionic conductivity without deteriorating mechanical properties. DETAILED DESCRIPTION

[0041] Hereinafter, for better understanding of the present disclosure, the present disclosure will be described in more detail.

[0042] The terms or words used in the specification and the appended claims should not be construed as limited to the ordinary or dictionary meanings, but should be interpreted in the present disclosure with meanings and concepts consistent with the technical ideas of the present disclosure based on the principle that the inventor can appropriately define the concepts of the terms to appropriately describe his own invention in the best manner.

[0043] As used herein, the term "bond", i.e., with respect to the conformation of a polar compound "bonded" to a polymer chain (e.g., a chain of a PEO-based copolymer), the term "bond" broadly refers to a conformation of a gaseous polar compound (which is a polar solvent molecule) being fixed to a polymer chain by vapor deposition of a polar solvent. In other words, the "bond" is not limited to a specific type of physical bond, chemical bond, etc., but refers to a state of being fixed by various bonds including physical bonds, chemical bonds, etc., or a state of being simply attached and fixed (e.g., by adsorption, etc.), or a state of being contained in a three-dimensional network structure formed by polymer cross-linking and being located near a polymer chain or a cross-linking structure and being fixed.

[0044] The term "three-dimensional network structure" used herein is a structure including a three-dimensional framework and an internal space formed by the framework, wherein the framework may include polymer chains including cross-links formed by cross-linkable functional groups, for example, cross-links between cross-linkable functional groups and / or cross-links between cross-linkable functional groups and cross-linking agents. The three-dimensional network structure may also be referred to as a cross-linked structure.

[0045] In the present disclosure, the polar compound (polar solvent) exists or is contained in the polymer solid electrolyte in a "gaseous state" indicates that, unlike the case where the polar solvent or the electrolyte containing the polar solvent is injected in a liquid state, the polar compound is deposited in a vapor state, and the polar compound exists in a state different from the liquid-injected electrolyte just after the polymer solid electrolyte is prepared or during the charging and discharging process of the all-solid-state secondary battery containing the polymer solid electrolyte. However, depending on the storage or operating conditions of the polymer solid electrolyte and / or the secondary battery, the vapor-deposited polar compound may have a partially or temporarily liquefied state. Even in this case, the vapor-deposited polar compound exhibits higher mobility than the polar solvent injected in a liquid state, and exhibits a state different from the liquid polar solvent, which can also be considered to be present or contained in the above-mentioned "gaseous state".

[0046] On the other hand, conventionally, in order to improve the ionic conductivity of the solid electrolyte, the solid electrolyte is immersed in or loaded on a liquid electrolyte or solvent, or the liquid electrolyte or solvent is directly injected into the solid electrolyte in a liquid state. When the liquid electrolyte or solvent is directly added to the solid electrolyte in this way, it has the effect of improving the ionic conductivity of the solid electrolyte, but this is only based on the high ionic conductivity of the liquid itself to improve the ionic conductivity of the solid electrolyte, and the degree of improvement is not sufficient, and a large amount of liquid electrolyte needs to be injected. In other words, since the conduction of lithium ions is achieved by the liquid electrolyte added to the solid electrolyte rather than the inherent physical properties of the solid electrolyte, it is far from improving the physical properties of the solid electrolyte itself. In addition, when the liquid electrolyte or solvent is directly added or injected into the solid electrolyte in liquid form, there is the following problem: due to the undesirable side reaction between the polymer and the liquid phase, the structure of the solid electrolyte collapses, such as the polymer chain is damaged or the polymer internal bond is broken, or the ionic conductivity is reduced.

[0047] In addition, when solvents or liquid electrolytes are directly injected into solid electrolytes, the liquid molecules diffuse rapidly within the solid electrolyte, rapidly causing relaxation of the polymer chains and promoting surface gelation, which may lead to a decrease in mechanical properties, and problems such as liquid leakage of the liquid electrolyte may not be completely solved.

[0048] In addition, Japanese Patent Application Laid-Open No. 1994-124713 as a prior art discloses a technique of vapor-depositing a solvent on a general PEO (polyethylene oxide) polymer. In this case, there is a problem that the internal structure of the polymer collapses due to lack of a cross-linked structure and ion conductivity cannot be ensured.

[0049] Therefore, the inventors have applied a method of vapor-depositing a polar compound derived from a polar solvent onto a polymer solid electrolyte containing a polymer cross-linked with a PEO (polyethylene oxide) copolymer modified with a cross-linkable functional group. A polymer solid electrolyte of one embodiment prepared in this manner includes: a polymer containing a PEO (polyethylene oxide) copolymer containing a cross-linkable functional group; and a polar compound, wherein at least a portion of the cross-linkable functional groups form cross-links with each other so that the polymer forms a three-dimensional network structure, and wherein the polar compound is contained in the three-dimensional network structure in a gaseous state or can represent a structure bonded to a polymer chain.

[0050] It was confirmed that the polymer solid electrolyte exhibited improved ion conductivity while containing a trace amount of gaseous polar compounds derived from polar solvents. It is expected that this is because the gaseous polar compounds affect the physical properties such as crystallinity of the PEO-based copolymer and increase the chain mobility of the polymer chain, thereby improving the conductivity of lithium ions contained in the polymer solid electrolyte.

[0051] Therefore, the polymer solid electrolyte of one embodiment exhibits improved ion conductivity without substantially containing a liquid polar solvent or electrolyte, and can greatly contribute to the development of all-solid-state batteries having excellent physical properties.

[0052] Next, a polymer solid electrolyte according to an embodiment of the present disclosure will be described in detail.

[0053] Polymer solid electrolyte

[0054] As described above, a polymer solid electrolyte of one embodiment includes: a polymer comprising a PEO (polyethylene oxide) type copolymer containing a cross-linkable functional group; and a polar compound, wherein at least a portion of the cross-linkable functional groups form cross-linked bonds with each other so that the polymer forms a three-dimensional network structure, and wherein the polar compound is contained in the three-dimensional network structure or bonded to the polymer chain in a gaseous state.

[0055] In a specific example, the gaseous polar compound may be dispersed between polymer chains forming a three-dimensional network structure, or may have a conformation of being adsorbed or bonded to the surface or interior of the polymer chain.

[0056] The polymer solid electrolyte contains trace amounts of polar compounds, which are contained or bonded in a gaseous state by vapor deposition to be described later. The polymer solid electrolyte can be confirmed from the following facts: for example, when the electrolyte layer containing the polymer solid electrolyte is separated from the all-solid-state battery and then observed with the naked eye or an electron microscope, no liquid component is observed on the surface of the electrolyte layer. In contrast, when a liquid polar solvent or electrolyte is injected into the polymer solid electrolyte, a liquid component or a component exhibiting wettability can be observed on the surface of the electrolyte layer. In addition, as confirmed by the embodiments described later, a polymer solid electrolyte of an embodiment in which a polar compound is vapor-deposited and contained in a gaseous state exhibits a significantly higher ionic conductivity than when a liquid polar solvent or electrolyte is injected. By comparison of this ionic conductivity, a polymer solid electrolyte in which a polar compound is vapor-deposited and contained in a gaseous state can be confirmed.

[0057] In the polymer solid electrolyte of one embodiment, the crosslinkable functional group can be directly bonded to the main chain of the PEO-based copolymer, or can be bonded by an alkylene or oxyalkylene linker. Therefore, the crosslinkable functional group can be bonded by an alkylene linker or an oxyalkylene linker having 0 to 10 carbon atoms (wherein the alkylene linker having 0 carbon atoms represents a single bond), and can be selected from at least one of the group consisting of a hydroxyl group, a carboxyl group, an isocyanate group, a nitro group, a cyano group, an amine group, an amide group, an epoxy group, and an allyl group.

[0058] In one embodiment of the present disclosure, the crosslinkable functional group may be composed of two or more. The crosslinkable functional groups may be the same or different from each other, and preferably may be different. When the crosslinkable functional groups are different, multiple repeating units each containing these functional groups may be included. In addition, when multiple crosslinkable functional groups are included, the mobility and ionic conductivity of the polymer chain can be more easily controlled.

[0059] The crosslinkable functional group refers to a functional group capable of forming a crosslink bond between crosslinkable functional groups and / or forming a crosslink bond with each other through a crosslinking agent, and may be bonded to the main chain of the polymer chain in the form of a side chain.

[0060] In a more specific example, the PEO-based copolymer containing a cross-linkable functional group may be a copolymer containing repeating units of the following Chemical Formulas 1 to 3:

[0061] [Chemical formula 1]

[0062]

[0063] [Chemical formula 2]

[0064]

[0065] [Chemical formula 3]

[0066]

[0067] Wherein, in Chemical Formulas 1 to 3, R1 represents -CH2-O-(CH2-CH2-O) k -R3, k is 0 to 20, R3 represents an alkyl group having 1 to 5 carbon atoms,

[0068] R2 represents a substituent formed by bonding one or more crosslinkable functional groups selected from the group consisting of a hydroxyl group, a carboxyl group, an isocyanate group, a nitro group, a cyano group, an amine group, an amide group, an epoxy group, and an allyl group to a polymer chain through an alkylene linker having 0 to 10 carbon atoms or an oxyalkylene linker (wherein an alkylene linker having 0 carbon atoms represents a single bond), and

[0069] l, m and n are the number of repetitions of the repeating unit, wherein l and n are each independently an integer from 1 to 1000, and m is an integer from 0 to 1000.

[0070] For example, the cross-linkable functional group of R2 can form a polymer in the form of a matrix having a three-dimensional network structure formed by cross-linking. By cross-linking to form a three-dimensional network structure, the mechanical properties of the polymer solid electrolyte can be improved, and a gaseous polar compound can be included or bonded in this three-dimensional network structure to provide a polymer solid electrolyte of one embodiment with improved ionic conductivity.

[0071] In addition, it is apparent that the PEO-based copolymer may include two or more repeating units of Chemical Formula 3, wherein R2 are cross-linkable functional groups different from each other, and may also include one or more repeating units of Chemical Formula 2.

[0072] When l, m and n are each less than 1, it is difficult to form a polymer due to the small molecular weight, and when l, m and n are each greater than 1000, the solubility during the preparation of the polymer solution decreases due to the increase in viscosity, and the molding for preparing the polymer solid electrolyte may become difficult. In particular, when the number of repetitions of the repeating unit containing a crosslinkable functional group in l, m and n is greater than 1000, the degree of crosslinking increases excessively, the mobility of the polymer chain may decrease, and the ionic conductivity of the polymer solid electrolyte may decrease.

[0073] As used herein, "hydroxy" refers to an -OH group.

[0074] As used herein, "carboxyl" refers to a -COOH group.

[0075] As used herein, "isocyanate" refers to a -N=C=O group.

[0076] As used herein, "nitro" refers to a -NO2 group.

[0077] As used herein, "cyano" refers to a -CN group.

[0078] As used herein, "amide" refers to -C(=O)NR'R", wherein R' and R" can each independently be hydrogen or C1 to C5 alkyl, or R' and R" together with the N atom to which they are attached can form a heterocycle having 4 to 8 carbon atoms in the ring structure.

[0079] As used herein, "amino" may be selected from the group consisting of monoalkylamino, monoarylamino, monoheteroarylamino, dialkylamino, diarylamino, diheteroarylamino, alkylarylamino, alkylheteroarylamino, and arylheteroarylamino, and the carbon number thereof is not particularly limited, but is preferably 1 to 30. Specific examples of amine include methylamino, dimethylamino, ethylamino, diethylamino, phenylamino, naphthylamino, biphenylamino, dibiphenylamino, anthracenylamino, 9-methyl-anthrylamino, diphenylamino, phenylnaphthylamino, ditolylamino, phenyltolylamino, triphenylamino, biphenylnaphthylamino, phenylbiphenylamino, biphenylfluorenylamino, phenyltriphenyleneamino, and biphenyltriphenyleneamino, but are not limited thereto. In addition, "amino" refers to -NH2.

[0080] As used herein, "allyl" refers to a -CH2-CH=CH2 group.

[0081] The weight average molecular weight (Mw) of the copolymer containing chemical formula 1 to 3 can be 100,000g / mol to 2,000,000g / mol, specifically, it can be 100,000g / mol or more, 200,000g / mol or more, or 300,000g / mol or more and 1,600,000g / mol or less, 1,800,000g / mol or less, or 2,000,000g / mol or less. If the weight average molecular weight (Mw) of the copolymer is less than 100,000g / mol, the mechanical properties of the polymer solid electrolyte to be prepared may not be met. If the weight average molecular weight (Mw) of the copolymer is greater than 2,000,000g / mol, the solubility during the preparation of the polymer solution is reduced due to increased viscosity, and the molding for preparing the polymer solid electrolyte may become difficult. In addition, due to the increase in crystallinity and the reduction in chain mobility inside the polymer solid electrolyte, the ionic conductivity of the polymer solid electrolyte may be reduced.

[0082] In particular, when the number of repetitions of the repeating unit of Formula 3 containing a crosslinkable functional group in l, m, and n is greater than 1000, the degree of crosslinking increases excessively and the mobility of the polymer chain decreases, thereby causing the ionic conductivity of the polymer solid electrolyte to decrease.

[0083] Furthermore, the copolymer may be a random copolymer or a block copolymer.

[0084] In a specific embodiment of the present disclosure, the polar compound may be contained in a gaseous state or bonded to the surface or interior of the polymer chain. Specifically, the gaseous polar compound may diffuse or disperse between the polymer chains that form a three-dimensional network structure by cross-linking, or may be adsorbed or bonded to the surface or interior of the polymer chain.

[0085] The polar compound is a gas molecule of a polar solvent used in the vapor deposition process, and may be included in a form in which the gas molecule of the polar solvent is adsorbed to the polymer during the vapor deposition, and then diffuses into the inside of the polymer chain and bonds to the polymer chain, or disperses or diffuses in the internal space between the polymer chains. The polar compound is bonded to the polymer chain or dispersed in the internal space between the polymer chains, thereby improving the ionic conductivity of the polymer solid electrolyte finally prepared.

[0086] Specifically, polar compounds bonded to or included between polymer chains can be used as plasticizers and plasticize the polymer. The plasticized polymer may have an increased amorphous region inside, which can improve the mobility of the polymer chain. As the mobility of the polymer chain increases, the ion hopping effect inside the polymer increases, which can improve the ionic conductivity of the polymer solid electrolyte.

[0087] In addition, polar compounds can be used as intermediates for smooth ion transport through ion hopping. Since the affinity between lithium ions and polar compounds is stronger than the affinity between lithium ions and the ether oxygen of PEO-based copolymers, the transmission of lithium ions within the polymer adsorbing polar compounds may be faster and easier. That is, as the polar compound flows into the interior of the polymer, the cationic solvation effect of lithium ions increases to improve ion mobility, thereby improving the ionic conductivity of the polymer solid electrolyte.

[0088] In addition, the polar compound may include at least one selected from the group consisting of carbonate-based compounds and sulfonyl-based compounds.

[0089] Specifically, the polar compound may include at least one selected from the group consisting of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC) and sulfolane, or a combination thereof.

[0090] Based on the gross weight of the polymer solid electrolyte, the content of the polar compound may include more than 0.1 wt % and less than 10 wt %. For example, the content of the polar compound may be more than 0.1 wt %, more than 1 wt % and less than 2 wt %, or less than 5 wt %, less than 6 wt %, less than 7 wt %, less than 8 wt %, or less than 9 wt %, or less than 10 wt %. When the content of the polar compound is less than 0.1 wt %, it is difficult to cause changes in the chain conformation inside the polymer, and therefore, the ionic conductivity of the polymer solid electrolyte is not improved. When the content of the polar compound is more than 10 wt %, the polymer solid electrolyte has a larger liquid content and has the performance of a semi-solid battery. In addition, due to the gelation of the polymer, the mechanical strength of the polymer solid electrolyte may be reduced.

[0091] In one embodiment of the present disclosure, the polymer solid electrolyte may include crosslinks between crosslinkable functional groups. In addition, the polymer solid electrolyte may further include a crosslinking agent to form crosslinks between the crosslinking agent and the crosslinkable functional groups. For example, at least a portion of the crosslinkable functional groups may form crosslinks with each other via a crosslinking agent, thereby forming the above-mentioned three-dimensional network structure.

[0092] The cross-linking bond may be a urethane cross-linking bond, an ester cross-linking bond, a hydrogen bond, a bond formed by a radical polymerization reaction of a vinyl group at the end of an allyl group (-CH2-CH=CH2), etc., but is not limited to these examples.

[0093] In addition, when a crosslinking agent is added during the preparation of the polymer solid electrolyte, a crosslinking bond between the crosslinking agent and the crosslinkable functional group can be formed. The crosslinking bond can be a hydrogen bond, a bond formed by Lewis acid-base interaction, an ionic bond, a coordination bond, or a bond formed by free radical polymerization.

[0094] The crosslinking agent is not particularly limited as long as it is a multifunctional crosslinking agent that can form a crosslinked bond with a crosslinkable functional group. For example, the crosslinking agent can be selected from trimethylolpropane trimethacrylate, poly(ethylene glycol) diacrylate, poly(ethylene glycol) dimethacrylate, ethylene glycol dimethacrylate (hereinafter referred to as "EGDMA"), 1,3-diisopropenylbenzene (DIP), 1,4-diacryl piperazine, 2-(diethylamino) ethyl methacrylate, 2,6-bisacrylaminopyridine, 3-(acryloyloxy)-2-hydroxypropyl methacrylate, 3,5-bis(acryloylamino) benzoic acid, 3-aminopropyl triethoxysilane, 3-isocyanatopropyl triethoxysilane, 3-methacryloxypropyl trimethoxysilane, bis-(1- (tert-butylperoxy)-1-methylethyl)-benzene, dicumyl peroxide, dimethacrylate, divinylbenzene, malein glycol acrylate, glycidyl methacrylate, hydroxyquinoline, i-phenyldiethoxysilane, malein glycol acrylate, methylenebisacrylamide, N,N'-1,4-phenylenedipropyleneamine, N,O-bisacryloyl-phenylalaninol, N,O-bismethacryloylethanolamine, pentaerythritol triacrylate, phenyltrimethoxysilane, tetramethoxysilane, tetramethylene compounds, tetraethoxysilane and triallyl isocyanurate. One or more polyfunctional crosslinking agents, for example, a difunctional or higher polyvalent compound.

[0095] In addition, the content of the crosslinking agent may be 1 to 30 parts by weight based on 100 parts by weight of the PEO-based copolymer containing a crosslinkable functional group. If the content of the crosslinking agent is less than 1 part by weight, crosslinking with the crosslinkable functional group may not be sufficiently achieved, and if the content of the crosslinking agent is greater than 30 parts by weight, excessive crosslinking may occur and the mobility of the polymer chain may be reduced, resulting in reduced ionic conductivity.

[0096] In one embodiment of the present disclosure, the polymer solid electrolyte may further include a lithium salt. The lithium salt is contained in the internal space between the polymer chains in a dissociated ionic state, and thus the ionic conductivity of the polymer solid electrolyte can be improved. At least a portion of the cations and / or anions dissociated from the lithium salt is maintained in a state bonded to the polymer chain, and can exhibit mobility during charge / discharge of the battery.

[0097] The lithium salt may include (CF3SO2)2NLi (lithium bis(trifluoromethanesulfonyl)imide, LiTFSI), (FSO2)2NLi (lithium bis(fluorosulfonyl)imide, LiFSI), LiNO3, LiOH, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, LiSCN, LiC(CF3SO2)3, lithium chloroborane, lower aliphatic carboxylic acid lithium and at least one of the group consisting of lithium tetraphenylborate.

[0098] In addition, based on 100 parts by weight of the PEO-based copolymer containing a crosslinkable functional group, the content of the lithium salt may be 25 to 45 parts by weight. Specifically, the content may be more than 25 parts by weight, more than 30 parts by weight, or more than 35 parts by weight, or less than 40 parts by weight, or less than 45 parts by weight. If the content of the lithium salt is less than 25 parts by weight, the ionic conductivity of the polymer solid electrolyte may be reduced, and if the content of the lithium salt exceeds 45 parts by weight, the mechanical strength may be reduced.

[0099] Preparation method of polymer solid electrolyte

[0100] In another embodiment of the present disclosure, the preparation method of the above-mentioned polymer solid electrolyte may include the following steps: (S1) preparing a polymer in which a PEO (polyethylene oxide) type copolymer containing a cross-linkable functional group is cross-linked; and (S2) vapor depositing a polar solvent on the polymer prepared in step (S1).

[0101] The description of the polymer cross-linked with the PEO-based copolymer having a cross-linkable functional group is the same as described above.

[0102] Each step is described in more detail below.

[0103] In step (S1), a polymer may be prepared in which a PEO (polyethylene oxide)-based copolymer containing a crosslinkable functional group is crosslinked.

[0104] The cross-linking reaction in step (S1) may be performed in the presence of at least one additive selected from the group consisting of a cross-linking agent and an initiator.

[0105] Furthermore, in order to form a polymer solid electrolyte, a lithium salt may also be added together in step (S1).

[0106] The cross-linking reaction can be performed by a process of coating a polymer solution containing a PEO-based copolymer on a substrate to form a coating film, and then drying the coating film.

[0107] Specifically, the polymer solution may be prepared by mixing the PEO-based copolymer in a solvent, and in addition, the solution may be prepared by mixing a cross-linking agent, an initiator, and / or a lithium salt together.

[0108] The solvent is not particularly limited as long as it is a solvent that can be mixed with the PEO-based copolymer, crosslinking agent, initiator and / or lithium salt and can be easily removed by a drying process. For example, the solvent can be acetonitrile, methanol, ethanol, tetrahydrofuran, water, isopropanol, dimethyl sulfoxide (DMSO), N-methyl-2-pyrrolidone (NMP) or N,N-dimethylformamide (DMF) and the like. This solvent is a solvent used as a reaction medium for forming a crosslinked bond, which is different from the polar solvent contained in the liquid electrolyte, and is completely removed by drying, etc. after crosslinking.

[0109] Considering the degree that the forming process of preparing polymer solid electrolyte can be carried out smoothly, the concentration of polymer solution can be appropriately adjusted. Specifically, the concentration of polymer solution can refer to the concentration (weight %) of polymer in polymer solution. The concentration of polymer can be the concentration of PEO-based copolymer. For example, the concentration of polymer solution can be 5 weight % to 20 weight %, specifically, it can be more than 5 weight %, more than 7 weight % or more than 9 weight % and less than 13 weight %, less than 17 weight % or less than 20 weight %. If the concentration of polymer solution is less than 5 weight %, the concentration may be too dilute, and the mechanical strength of polymer solid electrolyte may be reduced, or when coated on substrate, it may flow downward. If the concentration of polymer solution is greater than 20 weight %, it is difficult to dissolve lithium salt in polymer solution with desired concentration, viscosity will be high, solubility will be low, which makes it difficult to apply lithium salt in the form of uniform film.

[0110] The substrate is not particularly limited as long as it can be used as a support for coating. For example, the substrate can be SUS (stainless steel), polyethylene terephthalate film, polytetrafluoroethylene film, polyethylene film, polypropylene film, polybutylene film, polybutadiene film, vinyl chloride copolymer film, polyurethane film, ethylene-vinyl acetate film, ethylene-propylene copolymer film, ethylene-ethyl acrylate copolymer film, ethylene-methyl acrylate copolymer film or polyimide film.

[0111] In addition, the coating method is not particularly limited as long as it can form a coating film by coating the polymer solution on the substrate. For example, the coating method can be rod coating, roller coating, spin coating, slit coating, die coating, blade coating, comma coating, slit die coating, lip coating, spray coating or solution casting.

[0112] The coating film formed on the substrate by the coating method can be formed into a film-type polymer in which the residual solvent is completely removed by the drying process. Drying can be divided into a primary drying process and a secondary drying process to prevent the polymer from shrinking due to the rapid evaporation of the solvent. The primary drying process can remove part of the solvent by room temperature drying, and the secondary drying process can completely remove the solvent by vacuum high temperature drying. High temperature drying can be carried out at a temperature of 80°C to 130°C. If the high temperature drying temperature is less than 80°C, the residual solvent cannot be completely removed, and if the high temperature drying temperature is greater than 130°C, the polymer will shrink, which makes it difficult to form a uniform electrolyte membrane.

[0113] In addition, the crosslinking agent may form a bond with the crosslinkable functional group. The type of the crosslinking agent, the content of the crosslinking agent, and the type of bonding with the crosslinkable functional group are the same as described above.

[0114] In addition, the initiator can induce a free radical polymerization reaction between the crosslinkable functional groups to form a crosslinking bond between the crosslinkable functional groups. The functional group capable of free radical polymerization can be a functional group containing a vinyl group at the end, such as an allyl group.

[0115] The initiator is not particularly limited as long as it is an initiator that can induce a free radical polymerization reaction between crosslinkable functional groups. For example, the initiator may include at least one selected from the group consisting of benzoyl peroxide, azobisisobutyronitrile, lauroyl peroxide, cumene hydroperoxide, diisopropylphenyl-hydroperoxide, tert-butyl hydroperoxide, p-methane hydroperoxide and 2,2'-azobis(2-methylpropionitrile).

[0116] Based on 100 parts by weight of the PEO-based copolymer containing a crosslinkable functional group, the initiator may be used in an amount of 0.5 to 2 parts by weight. When the initiator is used within the above range, it may be able to induce a free radical polymerization reaction between the crosslinkable functional groups and effectively form a crosslink bond.

[0117] Otherwise, the content and type of lithium salt are the same as described above.

[0118] In step (S2), a polar solvent may be vapor-deposited on the polymer prepared in step (S1) to prepare the polymer solid electrolyte of one embodiment described above. At this time, the gas molecules of the polar solvent may be the polar compound included in one embodiment.

[0119] Vapor deposition can be carried out by contacting the polymer with the vapor of a polar solvent generated at room temperature or by heating and penetrating into the polymer. In this way, the gaseous polar compound is uniformly diffused on the surface and / or inside of the polymer by placing it at room temperature or by heated vapor deposition. The polar compound gas molecules may be bonded to the polymer chain, or may be contained in the internal space of the polymer chain in a uniformly dispersed or diffused form.

[0120] If the polar solvent is placed at room temperature during vapor deposition, a trace amount of the low-boiling-point polar solvent can slowly vaporize at room temperature and penetrate into the interior of the polymer, effectively inducing conformational changes in the cross-linked polymer chains within the polymer.

[0121] In addition, when the polar solvent is heated during vapor deposition, the vapor deposition rate can be increased. At this time, the heating temperature is not particularly limited, as long as it is a temperature at which the polar solvent can undergo a phase change into a vapor, for example, it can be 30°C to 80°C. General PEO melts at 60°C, but when a PEO-based copolymer modified with a crosslinkable functional group forms a crosslinked structure, its heat resistance is improved and can withstand up to 80°C, thereby further increasing the vapor deposition rate. In addition, the heating method is not limited, as long as it is a method that can supply energy to generate steam. For example, a direct heating method using a burner or a furnace or an indirect heating method using a heater or a steam pipe, etc., can be used, but the method is not limited to these examples.

[0122] During heating, if the temperature is too high, there are disadvantages that the solvent may boil at a temperature higher than the boiling point of the polar solvent, a structural change of the solvent may occur, or deformation of the polymer may be caused, and it is difficult to control the evaporation rate of the polar solvent during vapor deposition. For vapor deposition with a trace amount of a polar solvent, it is desirable to perform vapor deposition at a heating temperature within the appropriate range specified above.

[0123] All-solid-state battery

[0124] Another embodiment of the present disclosure also relates to an all-solid-state battery comprising the above-mentioned polymer solid electrolyte, wherein the all-solid-state battery comprises a negative electrode, a positive electrode and a polymer solid electrolyte between the negative electrode and the positive electrode, and the polymer solid electrolyte is based on the above-mentioned one embodiment.

[0125] Specifically, the polymer solid electrolyte includes a polymer cross-linked with a PEO (polyethylene oxide) type copolymer containing a cross-linkable functional group and a gaseous polar compound, and by including or bonding the gaseous polar compound, the ionic conductivity can be improved, which is suitable as an electrolyte for an all-solid-state battery.

[0126] On the other hand, the positive electrode included in the all-solid-state battery includes a positive electrode active material layer, wherein the positive electrode active material layer may be formed on one surface of a positive electrode current collector.

[0127] The positive electrode active material layer includes a positive electrode active material, a binder, and a conductive material.

[0128] In addition, the positive electrode active material is not particularly limited as long as it is a material that can reversibly absorb and desorb lithium ions, and examples thereof may be layered compounds such as lithium cobalt oxide, lithium nickel oxide, Li[Ni x Co y Mn z M v ]O2 (wherein M is any one selected from the group consisting of Al, Ga and In, or two or more thereof; and 0.3≤x<1.0, 0≤y, z≤0.5, 0≤v≤0.1 and x+y+z+v=1), Li (Li a M b-a-b' M' b' ) 2-c A c (wherein 0≤a≤0.2, 0.6≤b≤1, 0≤b'≤0.2 and 0≤c≤0.2; M includes Mn and at least one selected from the group consisting of Ni, Co, Fe, Cr, V, Cu, Zn and Ti; M' is at least one selected from the group consisting of Al, Mg and B; A is at least one selected from the group consisting of P, F, S and N), or a compound substituted with at least one transition metal; lithium manganese oxide, such as a chemical formula Li 1+y Mn 2-y O4 (where y is 0 to 0.33), LiMnO3, LiMn2O3 and LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, LiFe3O4, V2O5 and Cu2V2O7; chemical formula LiNi 1-y Ni-type lithium nickel oxide represented by MyO2 (wherein M is Co, Mn, Al, Cu, Fe, Mg, B or Ga, and y is 0.01 to 0.3); chemical formula LiMn 2-y M yLithium manganese composite oxides represented by Li2Mn3MO8 (wherein M is Co, Ni, Fe, Cr, Zn or Ta, and y is 0.01 to 0.1) or Li2Mn3MO8 (wherein M is Fe, Co, Ni, Cu or Zn); LiMn2O4 in which part of Li is replaced by alkaline earth metal ions; disulfides; and composite oxides formed by Fe2(MoO4)3, but are not limited thereto.

[0129] In addition, based on the total weight of the positive electrode active material layer, the content of the positive electrode active material may be 40 to 80 weight %. Specifically, the content of the positive electrode active material may be 40 weight % or more or 50 weight % or more, and 70 weight % or less or 80 weight % or less. If the content of the positive electrode active material is less than 40 weight %, the connectivity and electrical properties between the positive electrode active materials may be insufficient, and if the content of the positive electrode active material is greater than 80 weight %, the mass transfer resistance may increase.

[0130] The binder is a component that assists bonding between the positive electrode active material and the conductive material and bonding with the current collector. The binder may include at least one selected from the group consisting of styrene-butadiene rubber, acrylic styrene-butadiene rubber, acrylonitrile copolymer, acrylonitrile-butadiene rubber, nitrile rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinyl pyrrolidone, polyvinyl pyridine, polyvinyl alcohol, polyvinyl acetate, polyepichlorohydrin, polyphosphazene, polyacrylonitrile, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, cyanoethyl sucrose, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride and poly(vinylidene fluoride)-hexafluoropropylene. Preferably, the binder may include at least one selected from the group consisting of styrene-butadiene rubber, polytetrafluoroethylene, carboxymethyl cellulose, polyacrylic acid, lithium polyacrylate, and polyvinylidene fluoride.

[0131] In addition, based on the total weight of the positive electrode active material layer, the content of the binder may be 1 wt % to 30 wt %. Specifically, the content of the binder may be 1 wt % or more or 3 wt % or more, and 15 wt % or less or 30 wt % or less. If the content of the binder is less than 1 wt %, the adhesion between the positive electrode active material and the positive electrode current collector may be reduced, and if the content of the binder is greater than 30 wt %, the adhesion is improved, but the content of the positive electrode active material is correspondingly reduced, which may reduce the battery capacity.

[0132] In addition, the conductive material is not particularly limited as long as it does not cause side reactions in the internal environment of the all-solid-state battery and does not cause chemical changes in the battery but has excellent conductivity. The conductive material can generally be graphite or conductive carbon, and can be, for example, but not limited to, one selected from the group consisting of: graphite, such as natural graphite or artificial graphite; carbon black, such as carbon black, acetylene black, Ketjen black, Denka black, thermal black, channel black, furnace black, lamp black and summer black; carbon materials having a crystal structure of graphene or graphite; conductive fibers, such as carbon fibers and metal fibers; fluorocarbons; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive oxides, such as titanium oxide; conductive polymers, such as polyphenylene derivatives; and mixtures of two or more thereof.

[0133] Based on the total weight of the positive electrode active material layer, the content of the conductive material can generally be 0.5 wt % to 30 wt %. Specifically, the content of the conductive material can be more than 0.5 wt % or more than 1 wt %, and less than 20 wt % or less than 30 wt %. If the content of the conductive material is too low, i.e., less than 0.5 wt %, it is difficult to obtain the effect of improving conductivity, or the electrochemical characteristics of the battery may deteriorate. If the content of the conductive material is too high, i.e., greater than 30 wt %, the amount of the positive electrode active material is relatively small, so the capacity and energy density may be reduced. There is no particular limitation on the method for introducing the conductive material into the positive electrode, and conventional methods known in the prior art can be used, such as coating on the positive electrode active material.

[0134] In addition, the positive electrode current collector supports the positive electrode active material layer and plays a role in transferring electrons between the external wire and the positive electrode active material layer.

[0135] The positive electrode current collector is not particularly limited as long as it does not cause chemical changes in the all-solid-state battery and has high conductivity. For example, the positive electrode current collector can be made of the following materials: copper, stainless steel, aluminum, nickel, titanium, palladium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium or silver, or aluminum-cadmium alloy, etc.

[0136] In order to improve the bonding strength with the positive electrode active material layer, the positive electrode current collector may have a fine convex and concave structure layer on the surface or may adopt a three-dimensional porous structure. Thus, the positive electrode current collector may be used in any of various forms, including films, sheets, foils, grids, nets, porous bodies, foams, and non-woven fabric structures.

[0137] The positive electrode as described above can be prepared according to a conventional method. Specifically, the positive electrode can be prepared by the following process: a positive electrode active material layer-forming composition prepared by mixing a positive electrode active material, a conductive material and a binder in an organic solvent is coated on a positive electrode current collector and dried, and the current collector is optionally compression molded to increase the electrode density. At this time, as an organic solvent, it is preferred to use a solvent that can make the positive electrode active material, the binder and the conductive material uniformly dispersed and easily evaporated. Specifically, acetonitrile, methanol, ethanol, tetrahydrofuran, water, isopropanol, dimethyl sulfoxide (DMSO) and N-methyl-2-pyrrolidone (NMP) and the like can be mentioned.

[0138] On the other hand, the negative electrode included in the all-solid-state battery includes a negative electrode active material layer, and the negative electrode active material layer may be formed on one surface of a negative electrode current collector.

[0139] The negative electrode active material may include a material capable of reversibly inserting and deinserting lithium (Li + ) material, a material that can react with lithium ions to reversibly form a lithium-containing compound, lithium metal or a lithium alloy.

[0140] Able to reversibly insert and deintercalate lithium ions (Li + ) can be, for example, crystalline carbon, amorphous carbon, or a mixture thereof. + ) to reversibly form a lithium-containing compound may be, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).

[0141] Preferably, the negative electrode active material may be lithium metal, specifically, may be in the form of a lithium metal film or lithium metal powder.

[0142] The content of the negative electrode active material may be 40 to 80% by weight based on the total weight of the negative electrode active material layer. Specifically, the content of the negative electrode active material may be 40% by weight or more or 50% by weight or more, and 70% by weight or less or 80% by weight or less. If the content of the negative electrode active material is less than 40% by weight, the electrical characteristics may be insufficient, and if the content of the negative electrode active material is greater than 80% by weight, the mass transfer resistance may increase.

[0143] In addition, the binder is the same as described in the above-mentioned positive electrode active material layer.

[0144] In addition, the conductive material is the same as described in the above-mentioned positive electrode active material layer.

[0145] In addition, the negative electrode current collector is not particularly limited as long as it does not cause chemical changes in the corresponding battery and has conductivity. For example, the negative electrode current collector can be made of the following materials: copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with one of carbon, nickel, titanium or silver, or aluminum-cadmium alloy, etc. In addition, similar to the positive electrode current collector, the negative electrode current collector can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabric structures having fine protrusions and depressions formed on their surfaces.

[0146] The preparation method of the negative electrode is not particularly limited, and can be prepared by forming a negative electrode active material layer on the negative electrode current collector using a layer or film formation method commonly used in the art. For example, methods such as compression, coating, and deposition can be used. In addition, the negative electrode of the present disclosure also includes the case where the battery is assembled in a state where there is no lithium film on the negative electrode current collector and then a metal lithium film is formed on the metal plate by initial charging.

[0147] According to yet another embodiment, a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source are provided.

[0148] Here, specific examples of the device may include, but are not limited to: power tools driven by electric motors; electric vehicles, including electric vehicles (EV), hybrid electric vehicles (HEV) or plug-in hybrid electric vehicles (PHEV), etc.; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; or power storage systems, etc.

[0149] Preferred embodiments will be given below so that the present disclosure can be easily understood. However, the following embodiments are for illustrative purposes only, and the scope of the present disclosure is not limited thereto.

[0150] Example

[0151] Example 1: Preparation of polymer solid electrolyte

[0152] Step 1) Preparation of polymer containing copolymer

[0153] A polyethylene oxide (PEO) copolymer of the following chemical formula 1a was prepared:

[0154] [Chemical formula 1a]

[0155]

[0156] Wherein, in chemical formula 1a, R1 is -CH2-O-(CH2-CH2-O) k-CH3, R2 is -CH2-O-CH2-CH=CH2, k is 2, the ratio of l:m:n is 85:13:2, and the weight average molecular weight (Mw) of the copolymer is about 2,000,000 g / mol.

[0157] The copolymer of Chemical Formula 1a has an allyl group bonded through an oxymethylene linker as a crosslinkable functional group.

[0158] The polyethylene oxide copolymer was mixed with acetonitrile as a solvent, trimethylolpropane trimethacrylate as a crosslinking agent, benzoyl peroxide as an initiator, and LiTFSI as a lithium salt to prepare a polymer solution, which was then stirred for 24 hours using a magnetic bar. At this time, the polymer solution consisted of the following materials: based on 100 parts by weight of the polyethylene oxide copolymer, 20 parts by weight of trimethylolpropane trimethacrylate as a crosslinking agent, 1 part by weight of benzoyl peroxide as an initiator, and 36.5 parts by weight of a lithium salt, wherein the acetonitrile solvent was used so that the concentration of the polyethylene oxide copolymer as a polymer contained in the polymer solution was 10.4% by weight.

[0159] The prepared polymer solution was solution-cast on the lower substrate of the coin cell, and then dried once at room temperature for 12 hours and then dried twice at 100°C for 12 hours to induce cross-linking bonds, thereby preparing an electrolyte membrane with a thickness of 200 μm.

[0160] Step 2) Preparation of polymer solid electrolyte

[0161] The polymer was attached to the upper plate of the chamber, the lower part of the chamber was filled with ethyl methyl carbonate (EMC) solvent, and then naturally evaporated at room temperature for 72 hours to allow EMC vapor to flow into the polymer attached to the upper part of the chamber. Thus, a polymer solid electrolyte was prepared. Vapor deposition was performed so that the content of the EMC solvent was 1.2 wt % based on the total weight of the prepared polymer solid electrolyte.

[0162] Comparative Example:

[0163] Comparative Example 1: A polymer solid electrolyte containing only modified PEO (excluding solvent).

[0164] A polymer solid electrolyte was prepared in the same manner as in Example 1, except that step 2) of Example 1, i.e., the step of vapor-depositing the EMC solvent, was not performed.

[0165] Comparative Example 2: Polymer solid electrolyte containing modified PEO + a large amount of solvent

[0166] A polymer solid electrolyte was prepared in the same manner as in Example 1, except that a liquid solvent was directly injected into the polymer solid electrolyte prepared in step 1) of Example 1 without vapor deposition of an EMC solvent. The EMC solvent was directly injected so that the content of the EMC solvent was 12 wt % based on the total weight of the prepared polymer solid electrolyte.

[0167] Comparative Example 3: Unmodified PEO + polymer solid electrolyte deposited with polar solvent

[0168] A polymer solid electrolyte was prepared in the same manner as in Example 1, except that a polyethylene oxide (PEO) homopolymer (weight average molecular weight: about 4,000,000 g / mol) not substituted with a crosslinkable functional group was used, and no crosslinking agent or initiator was added. Vapor deposition was performed so that the content of the EMC solvent was 1.5 wt % based on the total weight of the prepared polymer solid electrolyte.

[0169] Experimental example

[0170] Experimental Example 1: Measuring the content of polar compounds

[0171] The content of the polar compound can be measured by using a balance and monitoring the weight of the liquid phase evaporated over time when the solid electrolyte sample is heated. For example, it can be measured by monitoring the weight of the liquid phase evaporated over time when the sample is heated at a temperature of 55 to 70°C or 60°C using a heated electronic balance (AND MS-70). When the amount of polar compound evaporated over time reaches saturation, the saturated amount at this time is considered to be the total amount of polar compounds contained in the solid electrolyte. In the embodiments and comparative examples, the polar compound can be ethyl methyl carbonate (EMC).

[0172] Experimental Example 2: Measuring the ionic conductivity of polymer solid electrolytes

[0173] In order to measure the ionic conductivity of the polymer solid electrolytes prepared in the examples and comparative examples, a 2 A polymer solid electrolyte was formed on the lower substrate of a coin cell, and then SUS was used as a blocking electrode to manufacture a coin cell for ion conductivity measurement.

[0174] The resistance was measured using an electrochemical impedance spectrometer (EIS, VM3, Bio Logic Science Instrument) at 25° C. with an amplitude of 10 mV and a scan range of 1 Hz to 0.1 MHz, and then the ionic conductivity of the polymer solid electrolyte was calculated using the following Equation 1.

[0175] [Equation 1]

[0176]

[0177] Wherein, in Equation 1, σi is the ionic conductivity of the polymer solid electrolyte (S / cm), R is the resistance of the polymer solid electrolyte measured by electrochemical impedance spectroscopy (Ω), L is the thickness of the polymer solid electrolyte (μm), and A refers to the area of ​​the polymer solid electrolyte (cm 2 The polymer solid electrolyte sample used had L = 200 μm, A = 1.7671 cm 2 .

[0178] Table 1 below shows the content of EMC vapor-deposited (or contained) in the polymer solid electrolyte and the measurement results of the ionic conductivity of the polymer solid electrolyte calculated using Equation 1.

[0179] [Table 1]

[0180]

[0181] It can be confirmed that the ionic conductivity of the modified PEO-based solid electrolyte (Comparative Example 1) and the solid electrolyte directly injected with liquid EMC (Comparative Example 2) is 10 -5 S / cm, while the ionic conductivity of the polymer solid electrolyte (Example 1) containing a gaseous polar solvent (EMC) in the modified PEO was increased to 10 -4 This is believed to be because, due to the vapor deposition of the polar solvent (EMC), the gaseous polar solvent compound diffuses into the cross-linked three-dimensional network structure of PEO or is adsorbed or bonded to the polymer chain, thereby improving the mobility of lithium ions.

[0182] On the other hand, for the general PEO-based solid electrolyte that is not cross-linked or modified as in Comparative Example 3, the effect of improving the ionic conductivity due to the vapor deposition of the polar solvent was not observed, and in particular, the internal structure of the polymer collapsed due to the lack of a cross-linked structure, confirming an internal short-circuit state in which the ionic conductivity could not be measured. Therefore, it can be confirmed that in order to prepare a polymer solid electrolyte with improved ionic conductivity by the polar solvent vapor deposition process of the embodiment, a cross-linked structure and a three-dimensional network structure formed by a modified PEO polymer capable of forming a cross-linked structure are required.

Claims

1. A polymer solid electrolyte comprising: A polymer comprising a PEO (polyethylene oxide) type copolymer containing a crosslinkable functional group; as well as Polar compounds, wherein at least a portion of the cross-linkable functional groups form cross-links with each other, so that the polymer forms a three-dimensional network structure, and The polar compound is contained in the three-dimensional network structure in a gaseous state or bonded to a polymer chain.

2. The polymer solid electrolyte according to claim 1, wherein The polar compound in a gaseous state is dispersed between polymer chains forming the three-dimensional network structure, or is adsorbed or bonded to the surface or inside of the polymer chains.

3. The polymer solid electrolyte according to claim 1, wherein The polymer solid electrolyte further includes a cross-linking agent.

4. The polymer solid electrolyte according to claim 3, wherein At least a portion of the cross-linkable functional groups form cross-linked bonds with each other through the cross-linking agent.

5. The polymer solid electrolyte according to claim 1, wherein The PEO-based copolymer contains two or more cross-linkable functional groups.

6. The polymer solid electrolyte according to claim 1, wherein The crosslinkable functional group is bonded to the PEO-based copolymer through an alkylene linker or an oxyalkylene linker having 0 to 10 carbon atoms, wherein the alkylene linker having 0 carbon atoms represents a single bond, and The cross-linkable functional group is selected from the group consisting of a hydroxyl group, a carboxyl group, an isocyanate group, a nitro group, a cyano group, an amine group, an amide group, an epoxy group, and an allyl group. 7 . The polymer solid electrolyte according to claim 1 , further comprising a lithium salt dispersed on the polymer forming the three-dimensional network structure.

8. The polymer solid electrolyte according to claim 1, wherein The PEO (polyethylene oxide) copolymer is a copolymer containing repeating units of the following chemical formulas 1 to 3: [Chemical formula 1] [Chemical formula 2] [Chemical formula 3] Wherein, in Chemical Formulas 1 to 3, R1 represents -CH2-O-(CH2-CH2-O) k -R3, k is 0 to 20, R3 represents an alkyl group having 1 to 5 carbon atoms, R2 represents a substituent formed by bonding one or more crosslinkable functional groups selected from the group consisting of a hydroxyl group, a carboxyl group, an isocyanate group, a nitro group, a cyano group, an amine group, an amide group, an epoxy group, and an allyl group to a polymer chain through an alkylene linker or an oxyalkylene linker having 0 to 10 carbon atoms, wherein the alkylene linker having 0 carbon atoms represents a single bond, and l, m and n are the number of repetitions of the repeating unit, wherein l and n are each independently an integer from 1 to 1000, and m is an integer from 0 to 1000.

9. The polymer solid electrolyte according to claim 8, wherein The PEO-based copolymer includes two or more repeating units of Chemical Formula 3, wherein R2 are cross-linkable functional groups different from each other.

10. The polymer solid electrolyte according to claim 1, wherein The polar compound may be present in an amount of 0.1 wt % or more and less than 10 wt % based on the total weight of the polymer solid electrolyte.

11. The polymer solid electrolyte according to claim 1, wherein The polar compound includes at least one selected from the group consisting of carbonate compounds and sulfonyl compounds.

12. The polymer solid electrolyte according to claim 1, wherein The polar compound includes at least one selected from the group consisting of ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethylene carbonate (EC), propylene carbonate (PC), vinylene carbonate (VC) and sulfolane.

13. A method for preparing the polymer solid electrolyte according to claim 1, the method comprising the following steps: (S1) preparing a polymer, wherein a PEO (polyethylene oxide) type copolymer containing a crosslinkable functional group is crosslinked; as well as (S2) vapor-depositing a polar solvent onto the polymer prepared in step (S1).

14. The method for preparing a polymer solid electrolyte according to claim 13, wherein: The step (S1) is performed in the presence of at least one additive selected from the group consisting of a cross-linking agent and an initiator.

15. The method for preparing a polymer solid electrolyte according to claim 13, wherein: The polar solvent includes at least one selected from the group consisting of carbonate-based solvents and sulfonyl-based solvents.

16. The method for preparing a polymer solid electrolyte according to claim 13, wherein: In the step (S2), the vapor of the polar solvent is deposited on the polymer so that the content of the polar solvent is 0.1 wt % or more and less than 10 wt % based on the total weight of the polymer solid electrolyte.

17. An all-solid-state battery, comprising: positive electrode; a negative electrode; and An electrolyte layer interposed between the positive electrode and the negative electrode and comprising the polymer solid electrolyte according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • Manufacture of polymeric sold electrolyte

    JP1994124713A

  • Jump lope device

    KR1020220132764A

  • Novel bicyclic histone deacetylase inhibitors and pharmaceutical composition comprising the same

    KR1020230136061A